Security systems’ status with the use of technical means of video recording and video surveillance: international experience, perspectives for implementation in the activities of the National police of Ukraine - V. A. Korshenko; V. V. Chumak; M. V. Mordvyntsev; D. V. Pashniev (Law and Safety)
Search for criminals becomes more difficult in modern conditions of continuous growth of the population of big urban centers and more and more frequent use of the latest achievements of science and technology by criminals for the realization of their purposes and for counteraction to law enforcement agencies. To increase the efficiency of the search for offenders it is necessary to introduce the latest technologies. Therefore, the systems of video recording and video surveillance, which currently operate in Ukraine and are one of the areas of using these technologies, have been studied. It has been noted that the installed CCTV cameras mostly work in manual mode. The employee of the information processing center must watch the video in order to gather evidence and search for suspects. It takes a lot of time and requires the involvement of a large number of staff, which makes the search for criminals and obtaining evidence from video surveillance systems ineffective.